2019
DOI: 10.1021/acs.iecr.9b02141
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Saving Ionic Liquid-Based Extractive Distillation Configurations for Separating Ternary Azeotropic System of Tetrahydrofuran/Ethanol/Water

Abstract: The application of ionic liquids in separating complex ternary azeotropic system via extractive distillation (ED) is investigated. Five configurations using 1-butyl-3-methylimidazolium dicyanamide ([BMIM]­[DCA]) as entrainer are proposed for separating tetrahydrofuran/ethanol/water, including heat-integrated ternary extractive distillation (HITED), HITED under reduced pressure (HITEDRP), and three heat pump-assisted ternary extractive distillation (HP-TED 1, HP-TED 2 and HP-TEDRP) configurations. A multi-objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 73 publications
0
9
0
1
Order By: Relevance
“…Distilasi ekstraktif merupakan metode paling efektif yang digunakan di industri untuk memisahkan titik azeotrop seperti campuran isopropil alkohol-air karena dapat menghemat pemakaian energi dan ekonomis [7]. Proses pemisahan distilasi ekstraktif dibantu dengan menambahkan suatu zat ketiga [8].…”
Section: Pendahuluanunclassified
“…Distilasi ekstraktif merupakan metode paling efektif yang digunakan di industri untuk memisahkan titik azeotrop seperti campuran isopropil alkohol-air karena dapat menghemat pemakaian energi dan ekonomis [7]. Proses pemisahan distilasi ekstraktif dibantu dengan menambahkan suatu zat ketiga [8].…”
Section: Pendahuluanunclassified
“…At present, group definition, group parameters, and group interaction parameters of the UNIFAC-Lei model have been proved to be reliable for process simulation. Third is use of CAMD methods based on predicting models for screening of ILs with excellent performances. , At the process unit level, many works have used process simulation, analysis, synthesis, optimization, and control tools to verify the industrial feasibility and economic performances of IL processes. Aspen Plus software based on the NRTL or UNIFAC-Lei model is often used in process simulations. In order to achieve energy conservation and carbon emission reduction, various energy-saving methods have been applied to the IL extractive distillation processes, such as heat pump, heat integration, dividing of the wall column, hybrid processes, and thermally coupled schemes …”
Section: Introductionmentioning
confidence: 99%
“…Qi et al found that 1-alkyl-3-methylimidazolium hexafluorophosphate ([BMIM]­[PF 6 ]) was 2.4 times more effective than the organic solvent (sulfolane) in separating benzene from cyclohexane for extraction, and the negligible vapor pressure made it extremely easy to recycle, avoiding loss of extractant and secondary contamination of the product. Lei et al used 1-ethyl-3-methylimidazolium acetate ([EMIM]­[AC]) to capture volatile organic compounds (VOCs) in the pharmaceutical industry, and an industrial scale VOC capture process was established, whose results showed that the removal rates of dichloromethane and ethanol were as high as 91.82 and 97.01%, respectively. In addition, the total heat load of the IL process was low with increased degree of greening.…”
Section: Introductionmentioning
confidence: 99%